The prevalence of post-extraction complications in an outpatient dental clinic in Kuala Lumpur Malaysia--a retrospective survey - Jaafar, N.; Nor, G.M. (2000)
The aim of this retrospective study is to report on the prevalence of post-extraction complications among patients attending the Oral Surgery outpatient clinic of the Faculty of Dentistry, University of Malaya over a 12-month period from January to December, 1992. The prevalence of post-extraction complications which required further treatment was only 3.4 (n = 100), out of a total of 2968 patients who had extraction of one or more permanent teeth. Analysis based on complete clinical reports (n = 79) showed that dry socket accounted for nine out of ten cases of post-extraction complications. However the aetiology was largely unknown. No obvious association with medical history could be made. Lower teeth were more likely to have complications. The most common teeth associated with dry socket were the molars (76) and premolars (19). The most common molars to be affected are the first, followed by the third and lastly the second molars. A brief review of current aetiological factors of dry socket was discussed.